PENINGKATAN PENGETAHUAN ERGONOMI DAN KETERAMPILAN PEREGANGAN OTOT LEHER UNTUK MENCEGAH NYERI LEHER - Yanti Harjono Hadiwiardjo; Mila Citrawati (Universitas Majalengka, 2021)
Fourth grade medical faculty students of Pembangunan Nsional Univrsity (UPN) had longer duration of sitting in front of laptop and computers due to scientific writing. This condition caused musculoskeletal pain especially neck pain, so there should be effort to avoid this complain. The effort to avoid neck pain was by couselling of ergonomics knowledge and muscular strecthing skill. Counselling was followed by 31 fourth grade students. After counselling there was increasing median knowledge score (before counselling the median score was 60 and after counselling median score was 70). The Wilcoxon test result showed p value = 0.001, it meant that there was difference of knowledge score before and after counselling. Meanwhile, result of muscular stretching exercise showed decreasing index score of disability caused by neck pain from 4 to 1. Wilcoxon test result showed p value = 0.001 which meant that there was difference between index score of disability caused by neck pain before and after ergonomics knowledge, neck muscular stretching, neck pain.